Memahami Konsep Audit melalui Interaksi Auditee-Auditor: Studi Fenomenologi pada Lembaga Amil Zakat dan Kantor Akuntan Publik - Andi Irfan; Mujahidin; Harkaneri (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
This study explores how the meaning of audit is constructed and reframed through the lived experiences of auditor–auditee interactions within faith-based financial institutions. Five key themes emerged: (1) auditing serves to uphold trust between stakeholders and religious accountability; (2) auditors prioritize professional integrity, piety, and social responsibility; (3) audit quality stems from trustworthiness, sincerity, honesty, and courage; (4) auditor satisfaction encompasses both material and spiritual dimensions; and (5) auditing represents service rather than power over others. Adopting a phenomenological approach, this study captures the essence of the interactive processes between auditors and auditees, revealing that audit meaning transcends regulatory accountability to embody moral responsibility, mutual trust, and shared spiritual values. By integrating social interactionism and Islamic ethical perspectives, this research contributes to a broader conceptualization of auditing as a human-centered and spiritually informed practice. The study provides a holistic understanding of audit conceptualization, integrating the professional, ethical, and spiritual dimensions that shape audit practice and philosophy, and offers insights to enhance audit effectiveness and professional development.